Use of Coreceptors Other Than CCR5 by Non-Syncytium-Inducing Adult and Pediatric Isolates of Human Immunodeficiency Virus Type 1 Is Rare In Vitro - Zhang, Yi-jun (American Society for Microbiology, 1998)
We have tested a panel of pediatric and adult human immunodeficiency virus type 1 (HIV-1) primary isolates for the ability to employ the following proteins as coreceptors during viral entry: CCR1, CCR2b, CCR3, CCR4, CCR5, CCR8, CXCR4, Bonzo, BOB, GPR1, V28, US28, and APJ. Most non-syncytium-inducing isolates could utilize only CCR5. All syncytium-inducing viruses used CXCR4, some also employed V28, and one (DH123) used CCR8 and APJ as well. A longitudinal series of HIV-1 subtype B isolates from an infected infant and its mother utilized Bonzo efficiently, as well as CCR5. The maternal isolates, which were syncytium inducing, also used CXCR4, CCR8, V28, and APJ.